An Undiagnosed Ventricular Septal Rupture Presenting as New Onset Heart Failure: A Rare Complication of an Anterior Myocardial Infarction - Ryan T. Nguyen; Priyanka Satish; Marvin D. Atkins Jr; Sachin S. Goel (Methodist DeBakey Cardiovascular Journal)
Ventricular septal ruptures (VSR) are a rare but fatal complication of acute myocardial infarctions. We present a patient complaining of new onset heart failure symptoms that were found to be secondary to a new ventricular septal rupture from a recently undiagnosed anterior myocardial infarction. The patient underwent successful VSR patch repair with eventual recovery. This case highlights the importance of early diagnosis of VSR and reviews management options and appropriate timing for intervention.